“Sound and safe”: The effect of ambient sound on the perceived safety of public spaces - Sayin, Eda; Krishna, Aradhna; Ardelet, Caroline; Briand Decré, Gwenaëlle; Goudey, Alain (Elsevier, 2015)
The amount of crime to which individuals are exposed on a daily basis is growing, resulting in increased anxiety about being alone in some public places. Fear of crime usually results in avoidance of places that are perceived to be unsafe, and such avoidance can have negative financial consequences. What can be done to reduce fear in relatively safe public places that are nevertheless perceived as being unsafe? In this paper, we explore the effect of auditory input (type of ambient sound) on perceived social presence and one's feeling-of-safety in public spaces such as car parks and metro stations. In one field study and four laboratory studies, we demonstrate that different ambient sounds convey social presence to a different degree. When perceived social presence is higher and positive, the feeling-of-safety is also higher. Additionally, we show that an increase in perceived safety has a positive effect on consumers' satisfaction with the public area and even raises their willingness to purchase a monthly membership card for the public area. Furthermore, the effect of ambient sound on such consumer responses is serially mediated by perceived social presence and feeling-of-safety.
Keywords: Audition; Sound; Social presence; Perceived safety; Ambience